UI UX DEVELOPER: PENGEMBANG UI UX - Sofyan Mufti Prasetiyo; Hotmaida Simanjuntak; Dimas Bayu Laksono; Muhammad Gilang Nanda Gunawan (Shofanah Media Berkah, 2022)
In the current era of globalization, technological developments are a very influential requirement for the development of business and industrial companies. Therefore, it is not surprising that in the current era, many digital products are developing that are spread across various virtual platforms, both in the form of websites and applications. In designing a digital product, collaboration from several teams/professions is required, one of which is the User Interface/User Experience Developer or the UI/UX Developer profession. UI/UX developers are more focused on working in the digital area, namely designing digital products such as websites, applications, interactive television, landing pages, and dashboards. Keywords: User Interface, User Experience, Developer, Digital Product, Design